2023
DOI: 10.1002/adma.202303357
|View full text |Cite
|
Sign up to set email alerts
|

Flagella of Tumor‐Targeting Bacteria Trigger Local Hemorrhage to Reprogram Tumor‐Associated Macrophages for Improved Antitumor Therapy

Abstract: Tumor‐associated macrophages (TAMs) exhibit an immunosuppressive M2 phenotype and lead to failure of antitumor therapy. Infiltrated erythrocytes during hemorrhage are recognized as a promising strategy for polarizing TAMs. However, novel materials that precisely induce tumor hemorrhage without affecting normal coagulation still face challenges. Here, tumor‐targeting bacteria (flhDC VNP) are genetically constructed to realize precise tumor hemorrhage. FlhDC VNP colonizes the tumor and overexpresses flagella dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…ART is a water-soluble derivative of artemisinin and intravenous ART is first-line therapy for severe malaria and cerebral malaria [20][21][22]. It is a prodrug that is rapidly metabolized under biological conditions into its active form, dihydroartemisinin (DHA) [23][24][25][26][27]. Previous research revealed that the mechanism that ART induces mitophagy through the PINK1-dependent pathway is to facilitate the stabilization of the full-length version of PINK1 on the mitochondria, while concurrently activating the pathway dependent on PINK1 [28].…”
Section: Introductionmentioning
confidence: 99%
“…ART is a water-soluble derivative of artemisinin and intravenous ART is first-line therapy for severe malaria and cerebral malaria [20][21][22]. It is a prodrug that is rapidly metabolized under biological conditions into its active form, dihydroartemisinin (DHA) [23][24][25][26][27]. Previous research revealed that the mechanism that ART induces mitophagy through the PINK1-dependent pathway is to facilitate the stabilization of the full-length version of PINK1 on the mitochondria, while concurrently activating the pathway dependent on PINK1 [28].…”
Section: Introductionmentioning
confidence: 99%